The Deterrent Effects of Punishments for Noncompliance and Rewards for Compliance: A Comparison of Hospital Employees in Japan and the United States. Issue 9 (1st September 2016) - Kobayashi, Emiko; Kerbo, Harold R.
ABSTRACT: We integrate social learning theory into Grasmick's extended model of deterrence to propose that rational actors, in their decision of workplace deviance, consider not only possible costs of noncompliance but possible rewards of compliance. A review of the literature on cultural differences between Japan and the United States leads to the hypotheses that although perceived costs of noncompliance and rewards of compliance operate as deterrents across the two cultures, the deterrent effects of the costs and rewards are stronger and weaker, respectively, in Japan than the U.S. Analysis of survey data from hospital employees provides mixed support for our arguments.